The impact of standardized training curriculum in terms of pulse in the development of speed and bearing of achievement in swimming the 100-meter free for youth - Abdul-Jabbar, Farqad (Journal of Physical Education, 2011)
The importance of research in the use of modern equipment and advanced to measure the index pulse directly (field) in the regulation of pregnancy training, and a cornerstone for the training of the sport of swimming through the application of the training curriculum based on scientific grounds, the research problem lies in that the legalization of contraception training using modern equipment and advanced measure the pulse rate during training is not used previously in the sport of swimming training in Iraq. The research aims to: 1 - Identifying the training load to regulate the terms of the pulse, using monitoring devices on the pulse rate according to the training curriculum. 2 - Identifying the training load to regulate the carrying speed in the development and achievement of the pool (100 m) are free to young people (15-17) years. As for the hypotheses were: 1 - There are significant differences between the moral tests of tribal and ex-post index pulse, and for the post-test sample. 2 - There are significant differences between the moral tests of tribal and dimensional, and for post-test to test with the speed and performance for swimming (100 m) is free. In the research methodology and procedures of the field researcher has chosen the experimental method designed one group, and consisted of the sample (10) represent the national team swimmers to swim the youth Olympic Games, also included on the tests before and after the research sample. As for the main conclusions were: 1 - resulted in rationing exercises carry your speed through the field using a pulse monitor pulse rate to develop the index pulse in the tests with your speed (75 m), and achievement in the pool (100 m) is free. 2 - The legalization of contraception in terms of pulse training to work on the development of a recipe with speed in free-swimming test for a distance (75 m) any of the distance from the minimum effective distance (100 m) freestyle. 3 - has systematized training to withstand the speed your development in the digital level to complete the pool (100 m) free for young people. The main recommendations: 1 - need to adopt a systematized training curriculum prepared by the researcher in training young swimmers to develop a recipe with speed in the sport of swimming. 2 - dependence on the index pulse to the codification of pregnancy as the training gives a true indication of the reversal training on internal overload. 3 - Use of modern devices and techniques that measure physiological indicators in the field training in the codification of pregnancy, instead of traditional methods and techniques in training.